Merdeka Curriculum: Encouraging Creativity and Innovation of Islamic Religious Education Teachers in Madrasah - Asfiati, Asfiati (Al-Hayat: Journal of Islamic Education, 2023)
The Merdeka Curriculum is a new curriculum in Indonesia that gives teachers the freedom to develop learning materials and methods that suit students' needs. This research aims to examine the influence of the Merdeka Curriculum on the quality of Islamic Education (PAI) learning. This research uses qualitative methods to understand how the implementation of the Merdeka Curriculum encourages PAI teacher creativity and innovation in three different State Madrasah Aliyah (MAN) schools in the big cities of Medan, Padang and Bukittinggi. Data collection was carried out through in-depth interviews, classroom observations, and study of related documents. Merdeka Curriculum, data analysis was carried out using thematic, narrative and comparative analysis techniques. The research sample consisted of PAI teachers who had implemented the Merdeka Curriculum for more than one year and had sufficient teaching experience. The research results show that the Merdeka Curriculum has positive potential in improving the quality of PAI learning, including a more open and flexible learning approach, the relevance of learning to everyday life, as well as developing the character and ethics of students. However, the implementation of the Merdeka Curriculum in PAI learning also faces several challenges, such as teacher competency and readiness, support from each government and schools in each region, as well as the availability of resources. Comprehensive support from various parties, including government, schools and teachers, is needed to overcome these challenges.